2024
DOI: 10.1001/jamadermatol.2023.5550
|View full text |Cite
|
Sign up to set email alerts
|

Federated Learning for Decentralized Artificial Intelligence in Melanoma Diagnostics

Sarah Haggenmüller,
Max Schmitt,
Eva Krieghoff-Henning
et al.

Abstract: ImportanceThe development of artificial intelligence (AI)–based melanoma classifiers typically calls for large, centralized datasets, requiring hospitals to give away their patient data, which raises serious privacy concerns. To address this concern, decentralized federated learning has been proposed, where classifier development is distributed across hospitals.ObjectiveTo investigate whether a more privacy-preserving federated learning approach can achieve comparable diagnostic performance to a classical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Participants can train their local models using their proprietary data, and through iterative training, each participant contributes to the construction of a global model without sharing their data externally ( 78 ). This approach fosters collaboration among multiple medical institutions, facilitating the sharing of model learning outcomes ( 79 ).…”
Section: Models In Precision Diagnosis and Therapeutics For Ramentioning
confidence: 99%
“…Participants can train their local models using their proprietary data, and through iterative training, each participant contributes to the construction of a global model without sharing their data externally ( 78 ). This approach fosters collaboration among multiple medical institutions, facilitating the sharing of model learning outcomes ( 79 ).…”
Section: Models In Precision Diagnosis and Therapeutics For Ramentioning
confidence: 99%
“…Secure multiparty computation (25-27) and more recently, blockchain-based concepts (28-32) have also gained popularity to increase data security in privacy-preserving trustless systems. Although keeping data distributed across multiple sources is privacy-minded, performance of machine learning models still suffers in federated learning settings compared to conventional centralized learning (33)(34)(35). Therefore, another architectural approach is to accumulate data in a centralized point (i.e., a clinical data warehouse) with secure and privacy-oriented infrastructure.…”
Section: Collaboration During Data Analysismentioning
confidence: 99%
“…In our experience, system administrators of healthcare organizations are hesitant about this form of code execution on their environments even though there are containerized, mostly because they lack control over the code and thus data sovereignty becomes a concern. Furthermore, although the PHT could support a form of federated learning, studies have shown, that performance of ML models trained by federated learning can trail behind centrally trained models (33)(34)(35). Therefore, for optimal AI applications, data is required to be aggregated in a central point to train models to their full potential, for which key infrastructure is required.…”
Section: Collaboration During Data Analysismentioning
confidence: 99%